Constitutional Change and Referendums in Chile and Ireland: Faraway, So Close - Felipe Paredes; Alberto Coddou Mc Manus; Jane Suiter (Politics and Governance)
Chile and Ireland have held constitutional referendums in recent years. While Ireland has successfully passed several controversial constitutional amendments over the last decade, Chile has struggled with its proposed constitutional reform, with two unsuccessful national referendums in September 2022 and December 2023, leaving the constitutional debate unresolved. Both countries have shared challenges, such as constitutional blockage and political polarisation, and both have attempted to involve citizens in pre-referendum processes in various ways. Ireland has consolidated public participation and deliberation mechanisms despite recent setbacks, unlike Chile, which has relied on electoral innovations. So, how can these diverging outcomes be explained? This article proposes an explanation by comparing these two cases, highlighting the importance, possibilities, and limitations of constitutional referendums based on three criteria: the extent and intensity of change, the model of democratic participation, and the role of elites and incumbent powers. These three criteria are crucial for addressing constitutional change’s central challenges when linked to a referendum. Consequently, these criteria offer a focused analytical framework for understanding the explicit or implicit elements that can influence the success or failure of a constitutional referendum and must be considered in its design and organisation.